A Survey of Frozen Phantom Limb Experiences: Are Experiences Compatible With Current Theories - Collins, Kassondra L.; Robinson-Freeman, Katherine E.; O'Conor, Ellen; Russell, Hannah G.; Tsao, Jack W. (Frontiers in Neurology, 2018)
There are over two million individuals living with amputations in the United States. Almost all will experience the feeling of the amputated limb as still present, termed phantom limb sensation (PLS). Over 85% will also experience excruciatingly painful sensations known as phantom limb pain (PLP). Additionally some amputees also experience a sensation of the phantom limb in which the limb is immobile or stuck in a normal or abnormal anatomical position, termed frozen phantom sensations. When an amputee experiences a frozen limb they report that they are unable to move the limb, and sometimes report sensations of cramping and pain along with this immobility, fortunately not all frozen limbs are painful. Such sensations have previously been attributed to proprioceptive memories of the limb prior to amputation or a mismatch between visual feedback and proprioceptive feedback resulting from the initiation of a movement. Unfortunately there has been a dearth of research specifically focused on the frozen PLS. We conducted a survey to better elucidate and understand the characteristics and experiences of frozen PLSs. Results from the survey provided descriptions of a variety of frozen limb experiences, such as position and feelings experienced, combined with other phantom pain sensations, casting doubt on previous theories regarding frozen limbs. Further research needs to be focused on the etiology of phantom sensations and pain, which may not necessarily be maintained by the same processes, in order to understand better ways to treat PLP, increase mobility, and enhance amputees quality of life.